+0  
 
+5
206
1
avatar+36 

9^x+1 +3^2x+1=36. Solve fo x

Boniface  Feb 25, 2017
Sort: 

1+0 Answers

 #1
avatar+76870 
+5

9^(x+1) + 3^(2x+1)= 36

 

9^x * 9  + 3*3^(2x) = 36      divide by 3

 

3 * 9^x  + 3^(2x)  = 12

 

3 * 9^x + (3^2)^x  = 12

 

3 * 9^x + 9^x   =  12

 

9^x * (3 + 1)   = 12

 

9^x * 4   = 12      divide by 4

 

9^x  =   3

 

[3^2]^x  = 3^1

 

3^(2x)  = 3^1     equate exponents

 

2x  =  1    →  x  = 1/2

 

 

cool cool cool

CPhill  Feb 25, 2017

19 Online Users

avatar
avatar
avatar
avatar
We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details